2013
DOI: 10.1161/circimaging.113.000304
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Study Comparing Shunt Type in the Norwood Procedure for Single-Ventricle Lesions

Abstract: Background The Pediatric Heart Network’s (PHN) Single Ventricle Reconstruction Trial (SVR) randomized infants with single right ventricles (RV) undergoing a Norwood procedure to a modified Blalock-Taussig or RV-to-pulmonary artery shunt. This report compares RV parameters in the two groups using 3-dimensional echocardiography (3DE). Methods and Results 3DE studies were obtained at 10/15 SVR centers. Of the 549 subjects, 314 underwent 3DE studies at one to four time points (pre-Norwood, post-Norwood, pre-stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…27 Using both 2-and 3-dimensional echocardiography, those investigators showed no differences in RV function or the prevalence of significant TR between those undergoing mBTS and RV-PA conduit during the interstage period and up to age 14 months. 27,28 Considering the lack of a measurable difference between patients with those vastly different shunt physiologies, it is not surprising that we did not observe a difference between the VC and NVC groups.…”
Section: Discussionmentioning
confidence: 79%
“…27 Using both 2-and 3-dimensional echocardiography, those investigators showed no differences in RV function or the prevalence of significant TR between those undergoing mBTS and RV-PA conduit during the interstage period and up to age 14 months. 27,28 Considering the lack of a measurable difference between patients with those vastly different shunt physiologies, it is not surprising that we did not observe a difference between the VC and NVC groups.…”
Section: Discussionmentioning
confidence: 79%
“…Although quantitative assessment of RV function in HLHS by echocardiography is challenging, 3DE assessment of volumes and EF has been verified as a comparable method with CMRI even in HLHS patients and used in a multicenter clinical study. 7 In our study, we compared the RV volumes obtained with3D-STE with those from 3DE in HLHS patients after Fontan palliation, showing excellent correlations between them. From these results, we suggest that 3D-STE is as useful as 3DE for volume measurement in HLHS patients after Fontan palliation.…”
Section: Rv Volume Measurement In Hlhsmentioning
confidence: 86%
“…On the other hand, 3D echocardiography (3DE) has been shown to be a possible alternative for measuring RV volume in HLHS. [6][7][8][9] Additionally, 2D speckle-tracking echocardiography (STE) has been recognized as a useful method for assessing not only ventricular function but also the mechanics of ventricular function in HLHS. 10, 11 More recently, the advent of 3D-STE has allowed us to measure the 3D ventricular volumes and strains simultaneously in the left ventricle (LV).…”
mentioning
confidence: 99%
“…Several studies have previously confirmed this impairment of RV function and unfavorable change in RV size after S1P. A pair of secondary analyses of the SVR trial comparing indices between S1P surgical shunt types showed an increased BSA-indexed RV end-systolic volume, lower RV ejection fraction, and lower RV fractional area change from the post-S1P to pre-S2P echocardiogram (13, 19). Our findings confirm this but also demonstrate that digoxin may stabilize the fragile hemodynamics and lessen the expected RV dysfunction and dilatation seen during the interstage period.…”
Section: Discussionmentioning
confidence: 81%